Fulbright Foreign Language Teaching Assistant (Filipino) Scholars’ Journey in the United States of America - Maico Demi B. Aperocho; Candice Faye Kristen Lleses; Ryan Roi Domingo; Gianinna Elaine Labicane; Ma. Cristina Consuelo (CV. Literasi Indonesia, 2023)
Scholars under the Fulbright Foreign Language Teaching Assistant (FLTA) Program have three important roles: teach the Filipino language and culture, study two courses per semester, and serve as cultural ambassadors of the Philippines in the United States. Exploring the scholars’ journey is important in providing future scholars ideas on rewarding and challenging experiences. This qualitative-biographical study focuses on five scholars’ (2022-2023 cohort) personal embodied experiences and encounters of learning processes. Using reflective writing, introspection, and journal entries as data collection techniques, the researchers accounted for the journey of every scholar. Results show that scholars’ personal embodied experiences include a sense of fulfillment, challenges, and personal and professional growth while their encounters of learning processes are comprised of students’ challenges in learning the language, the presence of negative learning behavior, and appreciation of the language and culture taught. Scholars also see Fulbright as platform for global and cultural involvement and self-growth.